Patient Safety in Cross-border Care - Turk, Eva; Leyshon, Stephen; Pytte, Morten (Medicine, Law & Society, 2015)
Patient safety is a right and it raises particular issues in the context of cross-border care. Patients should be able to have trust and confidence in the healthcare structure as a whole; they must be protected from the harm caused by poorly functioning health systems, medical errors and adverse events. This paper addresses the state of cross-border healthcare in the European Union, the state of patient safety, the question of quality assurance and the role of accreditation as a risk based approach.
Keywords: patient safety; cross-border care; accreditation; healthcare; EU